The Formation of Bachelor’s Educational Content in Computer Science in Terms of Competence Approach - Манелюк, Аліна Володимирівна (Pedagogy of Higher and Secondary Education, 2017)
The article discusses approaches to the formation of the bachelors’ content of education in Computer Science. We have studied the issue of competencycharacteristics BS in Computer Science, considered the interpretation of the concept of «fundamentalization of education» in the scientific literature, the question of determining fundamental disciplines, as well as analyzed some aspects of bachelor of Computer Science in the UK, guidelines for determining the content of their training in Ukraine and abroad. Today, the real-time profile of training of future specialists requires mastering a set of relevant competences to perform functions within the area of training, which are necessary for this field. The common opinion of researchers who contributed to the analysis of educational programs and issues dealing withthe content of education is to provide basic vocational training and the formation of key competencies for professional future of employees of IT sector. The bachelors’ content of Computer Science is based on the regulations that exist today at the state level and correspond to advice of employers and competence-based approach. There is no unified viewpoint on the list of subjects proposed for undergraduate study. The key difference in the approach to the formation of learning content in domestic and educational context, such as in the UK, is the mphasis on professional competence, limiting the number of subjects taught and formation of a curriculum based on a personal professional development path. Further analysis requires such issues as variability of professional disciplines, the specifics of qualifications and their combination in universities of Great Britain, especially in the process of the pre-professional training obtaining the profession related to the IT sector.